Gene inversion potentiates bacterial evolvability and virulence - Christopher N. Merrikh (Nature Portfolio, 2018)
Head-on replication-transcription collisions occur within genes encoded on the lagging DNA strand. Here, the authors show that a large number of originally co-oriented (leading strand) genes have inverted to the head-on orientation, increasing both gene-specific mutation rates, and the overall evolvability of several bacterial pathogens.